Peran Mahasiswa Dalam Konsultasi Keuangan Untuk Peningkatan Laporan Keuangan Umkm Telur Gulung Pak Doni - Hana Putri Zoe; Mahesa Mahesa; Radhika Ayu Maulidia; Indri Basiru; M. Arsad Eka Adiyaksa; Sri Rahayuningsih (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to analyze the development and challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the production and marketing of rolled eggs in City X. Rolled eggs are one of the popular street foods with significant economic potential. The research method used is descriptive qualitative with a case study approach on several rolled egg MSMEs in the area.Recommendations resulting from this research include the need for government support in the form of training and access to funding, as well as enhancing collaboration among MSMEs to strengthen marketing networks. With the right strategies in place, it is hoped that rolled egg MSMEs can further develop and make a positive contribution to the local economy.